Literature review on hepatoprotective effects of diosgenin: possible mechanisms of action - Mohseni-Moghaddam, Parvaneh; Khanmohammadi, Manijeh; Roghani, Mehrdad (Frontiers in Pharmacology, 2023)
Liver diseases are among the major causes of death worldwide. Alcohol consumption, obesity, diabetes mellitus, viral infection, and drug-induced liver injury are common risk factors for the development of liver diseases. Diosgenin is a herbal steroidal sapogenin with hepatoprotective properties. This phytosteroid modulates lipid profile and prevents liver injury and fibrosis, metabolic associated fatty liver disease (MAFLD), steatohepatitis, and diabetes mellitus. Different mechanisms have been presented underlying the therapeutic properties of diosgenin. Diosgenin with antioxidant activity and ability to inhibit pro-inflammatory and apoptotic mediators as well as modulating gut microbiota is able to protect the liver. This literature overview summarizes the previously published studies regarding the hepatoprotective function of diosgenin against liver injury in different conditions with an emphasis on possible underlying mechanisms.